Theoretical perspectives on central chemoreception - intrinsic excitation-inhibition mechanisms in brainstem chemoreceptors (2016)
The aim of this work was to investigate intrinsic mechanisms of activation and inhibition of the C02 response in central chemoreceptors. We employed computational single neuron modeling to simulate the basic electrochemical behavior of individual chemoreceptors from the brainstem. The single-neuron model was developed following a Hodgkin-Huxley formulation characterized by a set of eleven mammalian C02/H+-sensitive ion currents: a voltage-sensitive Na+ current (INa), three Ca2+ currents (IL, IN, IT), inward and delayed rectifier K+ (Iir, Idr), two additional K+ currents (IA, IM), two Ca2+-sensitive K+ currents (ISK, IBK), and a hyperpolarization activated current (IH). We used the model to (i) simulate the general electrophysiological behavior of spontaneous chemosensitive neurons and their response to hypercapnic acidotic stimuli, (ii) to compute firing frequencies in response to different acidotic conditions, (iii) to study the effect of each ionic current on the firing rate, and (iv) to establish the role of the currents on the chemosensitive response. The results of this model give insights into the cellular mechanisms acting together to activate and modulate the C02/H* response of central chemoreceptors and argue in favor of additional braking pathways limiting the firing frequency by means of Ca2+-sensitive K+ current activation